PROBLEM BASED LEARNING BERBANTUAN GEOGEBRA UNTUK MENINGKATKAN BERPIKIR KRITIS DAN KEAKTIFAN BELAJAR - Saniyah, Siti Malihatus (Journal of Lesson Study in Teacher Education, 2025)
This research is motivated by the low learning outcomes of the students in class XI-1 at SMA Negeri 11 Semarang on the topic of geometric transformations. The critical thinking ability test in the pre-cycle showed that only 18 out of 36 students achieved mastery (50%) with an average score of 60. In addition to low critical thinking skills, student engagement in learning was also low. During lessons, some students slept in class, played with their phones, and lacked focus on the material being taught. It is hoped that the Problem-Based Learning (PBL) model assisted by Geogebra will improve student learning outcomes. The purpose of this classroom action research is to describe the implementation of the PBL model assisted by Geogebra in improving critical thinking skills and student engagement in learning geometric transformations in class XI-1 at SMA Negeri 11 Semarang for the 2024/2025 academic year. To achieve this goal, this research is designed in two cycles. The procedure in each cycle includes stages: planning, implementation, observation, and reflection. The data from the observations are described, interpreted, and then reflected upon to determine the corrective actions for the next cycle. The learning is considered successful if the percentage of students who achieve mastery in the class reaches the performance indicator, which is at least 85%. The classroom action research conducted in two cycles shows that the average score of students in the pre-cycle was 60, with a classical mastery rate of 19.44%. In cycle I, the average score increased to 74.42 with a classical mastery rate of 50%, and in cycle II, it increased to 86.39 with a classical mastery rate of 88.89%. Student engagement also improved after learning with the PBL model assisted by Geogebra, with the average engagement in cycle I being 73.78%. In cycle II, student engagement increased to an average of 89.63%. Based on the actions taken, it can be concluded that the PBL model assisted by Geogebra can improve the critical thinking skills and engagement of students in class XI-1 at SMA Negeri 11 Semarang.